(untitled) (Semiárida, 2019)
The objective of this work was to evaluate the influence of nitrogen fertilization on the expression of yield and grain protein content in wheat in different environments of the semiarid Pampa region. The field experiments were carried out in Embajador Martini, Macachín and Anguil. The treatments were: control (0N), fertilization at seeding with 40 kg N.ha-1 (40+0) and 80 kg N.ha-1 (80+0), delayed fertilization with 40 kg N.ha-1 (between Z3.9 and Z5.0) (0+40) and divided fertilization (40+40). The treatments were arranged in a completely randomized block design with four replicates. Five filed experiments were carried out in each site and yield, grain protein content, water use efficiency and nitrogen use efficiency were determined. The sites with IMO> 4.5% had more response to yields in comparation with control, than the sites with IMO> 4.5%. The soils with >50% A+L had grater soil potential fertility, and there were significant differences between the control and 80 kg.ha-1 at seeding o divided fertilization. Instead, the soils with <50% A+L did not show significant differences in the yields between treatments. The lowest yields in these soils were translated in higher protein grain content, reaching 11%. More soil nitrogen content increases the grain nitrogen content but decreases nutrient use efficiency. Although, rainfalls are the main restriction of this region, with a good water availability, the wheat productivity is limited by low nitrogen content.